2017
DOI: 10.4102/phcfm.v9i1.1405
|View full text |Cite
|
Sign up to set email alerts
|

Social support and coping in adults with type 2 diabetes

Abstract: BackgroundThe diagnosis of diabetes has been described as a lifelong psychological burden on the patient and his or her family. Social support plays a pivotal role in patients with diabetes and is important in enabling them to cope effectively with the disease. There is a dearth of research on social support and coping in patients with diabetes in South Africa.ObjectivesThe aim of this study was to explore whether patients with poor perceived social support have lower levels of well-being and coping than patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 39 publications
(47 reference statements)
6
49
0
16
Order By: Relevance
“…Social support (from family and healthcare providers) is also very important for maintaining lifestyle changes and effective diabetes self-management [ 11 ]. Increase in social support for adults with diabetes has been associated with a decrease in emotional distress, and individuals with high levels of social support have reported better levels of well-being ([ 12 ]. Thus, diabetes treatment does not only require medical treatment but psychosocial care to deal with diabetes-related emotional distress, and in some cases depression, which are commonly associated with diabetes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social support (from family and healthcare providers) is also very important for maintaining lifestyle changes and effective diabetes self-management [ 11 ]. Increase in social support for adults with diabetes has been associated with a decrease in emotional distress, and individuals with high levels of social support have reported better levels of well-being ([ 12 ]. Thus, diabetes treatment does not only require medical treatment but psychosocial care to deal with diabetes-related emotional distress, and in some cases depression, which are commonly associated with diabetes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO, adherence to treatment may be defined as the extent to which the patient’s history of therapeutic drug-taking coincides with the prescribed treatment [ 3 ]. Adherence to treatment remains a challenge in T2D since it is a chronic illness that is associated with a risk of comorbidity and requires a lifestyle change, especially after the onset of insulin therapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings have suggested that high levels of diabetes-specific distress may account for higher functional impairment, work loss, and poorer self-management behavior [ 17 19 ]. Decreasing emotional distress is important in helping the patient with diabetes to cope with the disease and improving adherence to treatment [ 3 ]. Furthermore, Fisher et al [ 20 ] identified seven major sources of distress among patients with type 1 diabetes, among them physician distress.…”
Section: Introductionmentioning
confidence: 99%
“…El cumplimiento y mantenimiento de estas complejas actividades, es especialmente difícil, si no se cuenta con apoyo, ya que muchas de estas actividades requieren de la colaboración por parte de la familia para lograrlas (preparación de alimentos equilibrados, acompañamiento en la actividad física, recordatorios para la citas con profesionales de la salud, etc.) (13,39) . La Teória específica sobre las Conductas familiares para la Autogestión y el Control glucémico de las personas con Diabetes, está integrada por cuatro conceptos.…”
Section: -55 2018; 3(7)unclassified